Green paper : action plan for telecommunications & ICT services in CARICOM : addressing convergence issues in a single market (CRNM Christ ChurchBB, 2006)
Proposes an Action Plan for telecoms services and convergence initiatives for development, trade and investment in CARICOM.
Keywords: TELECOMMUNICATIONS